Ethics and legal requirements for data linkage in 14 European countries for children with congenital anomalies - Babak Khoshnood; David Tucker; Susan Jordan; Hanitra Randrianaivo; Maria Loane; Ingeborg Barisic; Miriam Gatt; Kari Klungsoyr; Anna Pierini; Anke Rissmann; Joan K Morris; Clara Cavero-Carbonell; et al. (BMJ Open, 2023)
Introduction Linking healthcare data sets can create valuable resources for research, particularly when investigating rare exposures or outcomes. However, across Europe, the permissions processes required to access data can be complex. This paper documents the processes required by the EUROlinkCAT study investigators to research the health and survival of children with congenital anomalies in Europe.Methods Eighteen congenital anomaly registries in 14 countries provided information on all the permissions required to perform surveillance of congenital anomalies and to link their data on live births with available vital statistics and healthcare databases for research. Small number restrictions imposed by data providers were also documented.Results The permissions requirements varied substantially, with certain registries able to conduct congenital anomaly surveillance as part of national or regional healthcare provision, while others were required to obtain ethics approvals or informed consent. Data linkage and analysis for research purposes added additional layers of complexity for registries, with some required to obtain several permissions, including ethics approvals to link the data. Restrictions relating to small numbers often resulted in a registry’s data on specific congenital anomalies being unusable.Conclusion The permissions required to obtain and link data on children with congenital anomalies varied greatly across Europe. The variation and complexity present a significant obstacle to the use of such data, especially in large data linkage projects. Furthermore, small number restrictions severely limited the research that could be performed for children with specific rare congenital anomalies.